Perceived usefulness of Management Accounting system, budget participation, individual accountability and managerial performance : a study on Malaysian local authority / Sharifah Fadzlon Syed Abd Hamid ... [et al.] - Syed Abd Hamid, Sharifah Fadzlon; Mohd Sanusi, Zuraidah; Sulaiman, Latipah; Mohamad, Nafsiah (Institute of Research, Development and Commercialization (IRDC), 2006)
This paper examined the combined effect of perceived usefulness of Management Accounting System (MAS), budgetary participation and individual accountability on managerial performance. The data was collected using questionnaires addressed to 78 officers from five local authorities. The findings did not support the direct, effect of perceived usefulness of MAS on managerial performance. However, 'the findings revealed that high level of budgetary participation significantly influenced high level managerial performance. Similarly, the results also showed that high perceived level of individual accountability significantly influenced managerial performance.